Predicting the diurnal blue-sky albedo of soils using their laboratory reflectance spectra and roughness indices. (October 2017) - Cierniewski, Jerzy; Ceglarek, Jakub; Karnieli, Arnon; Królewicz, Sławomir; Kaźmierowski, Cezary; Zagajewski, Bogdan
Highlights: A model for predicting blue-sky albedo of soil with defined roughness is proposed. The model uses laboratory reflectance spectra of related soil samples. Best accuracy is given by the reflectance data transformed to 2nd derivative. Abstract: The objective of this study was to assess the relationship between the hyperspectral reflectance of soils and their albedo, measured under various roughness conditions. 108 soil surface measurements were conducted in Poland and Israel. Each surface was characterised by its diurnal albedo variation in the field as well as by its reflectance spectra obtained in the laboratory. The best fit to the model was achieved by post-processing manipulation of the spectra, namely second derivate transformation. Using a stepwise elimination process, four spectral wavelengths and the roughness index were selected for modelling. The resulting models allowed the albedo of a soil to be predicted for its different roughness states and any solar zenith angle, provided that hyperspectral reflectance data is available.